Sistem Kendali dan Monitoring Pada Rumah Pintar Berbasis Internet of Things (IoT) - Ruuhwan Ruuhwan; Randi Rizal; Indra Karyana (Innovation in Research of Informatics (INNOVATICS), 2019)
The Smart Home system consists of control, monitoring and automation devices that can be accessed from anywhere as long as there is an internet connection. In Smart Home, several devices or home appliances that can be accessed through android-based applications such as temperature monitoring, gas intensity, fire identification and automatic monitoring of door conditions. This research aims to design and create a smart home system based on the IoT concept. The research methodology uses an experimental methodology. The design of this system is made using an Android smartphone, Arduino microcontroller, Ethernet shield, relay module, fire sensor, temperature sensor (LM35), gas sensor (MQ6), and magnetic sensor. The results of this study are monitoring and control systems on smart homes by utilizing an already available Web service called Teleduino. This web service functions as an intermediary between an Android device and the Arduino microcontroller. The Arduino Microcontroller requires an additional device called the Ethernet Shield to connect Arduino to the Internet that is connected directly to the Teleduino web service.